Cytokine Profile in the Prognosis of Coronary Heart Disease Comorbidity in Chronic Obstructive Pulmonary Disease - Tashkenbaeva Eleonora Negmatovna; Farida Odylovna Khasanjanova; Khudoynazarov Daler Anvar ugli; Usarov Shokhrukh Abduvakhob ugli (Genius Journals, 2023)
The objective of the to determine the relationship between cytokine levels and the clinical course of CHD with COPD.
Keywords: cytokine levels